Pelaksanaan Hak Anak Pidana untuk Mendapatkan Pendidikan dan Pengajaran di lembaga Pembinaan Khusus Anak Klas II Tanjung Pati - Yustrisia, Lola (Pagaruyuang Law Journal, 2019)
This study aims to determine the implementation of the rights of criminal children to obtain Education and Teaching at the Child Development Foundation Class II of Tanjung Pati. The research method used in this study is empirical juridical which functions to see the law in the real sense. This research is descriptive qualitative based on material and data related to the topic of discussion. The author describes and explains the problem in accordance with the facts that occur through a number of factors relevant to this research and then draw conclusions. The formulation of the problem in this study is about: first, how is the implementation of the right of a criminal child to get education and teaching in the Child Development Foundation Class II of Tanjung Pati? Secondly, what are the obstacles in terms of the Implementation of the Rights of Criminal Children to Obtain Education and Teaching at the Child Development Foundation Class II Tanjung Pati? third, how is the effort to overcome the obstacles in terms of the implementation of the criminal rights for children to obtain education and teaching at the Child Development Foundation Class II of Tanjung Pati?.